Taking on Authorship: William Hutton's Testy Relationship to Literary Authority. Issue 3 (4th May 2017) - Ferris, Ina
ABSTRACT: This essay argues that William Hutton's singular literary career—launched late and from an unlikely background—was underwritten by an unorthodox understanding of what it meant to write history. Starting with his pioneering History of Birmingham in 1781, he reworked the protocols of historical and literary authorship by recasting history writing in an embodied, experiential mode that answered to his own condition as a new man in a new city, and turned less on the past than on zones of its intersection with the present.